The Influence of Thermomechanical Treatments on the Structure, Microstructure, and Mechanical Properties of Ti-5Mn-Mo Alloys - Lourenço, Mariana Luna [UNESP]; Pontes, Fenelon Martinho Lima [UNESP]; Grandini, Carlos Roberto [UNESP] (MDPI, 2022)
With the increase in the world’s population, the rising number of traffic accidents, and the increase in life expectancy, the need for implants, dental work, and orthopedics is growing ever larger. Researchers are working to improve the biomaterials used for these purposes, improve their functionality, and increase the human body’s life span. Thus, new titanium alloys are being developed, usually with β-stabilizer elements (which decrease the elastic modulus), with the Ti-MnMo alloys being one example of these. This study of the Ti-5Mn-10Mo and Ti-5Mn-15Mo alloys only showed signs of the β phase in the structure and microstructure, presenting a combination of low modulus of elasticity and high corrosion resistance compared to the values of commercial alloys. In this sense, this work presents an analysis of the influence of some thermomechanical treatments, such as homogenization, hot-rolling, solution, and annealing, on the structure, microstructure, and selected mechanical properties of the Ti-5Mn-10Mo and Ti-5Mn-15Mo alloys.
Keywords: Mechanical properties; Thermomechanical treatments; Ti alloys